High-specific-characteristic low-temperature secondary lithium battery and application thereof

By adopting a three-dimensional ordered shell-like structure silicon-based negative electrode material and a high-capacity lithium cobalt oxide positive electrode material, combined with a multi-functional electrolyte, the lack of performance of lithium-ion batteries in high specific energy and low temperature environments is solved, and the battery performance with high specific characteristics, long-term stable circulation and safety is achieved.

CN119725678APending Publication Date: 2025-03-28CHINESE PEOPLES LIBERATION ARMY UNIT 32181
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619473.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing lithium-ion batteries show shortcomings in high specific energy and low temperature environments, especially the structural stability and conductivity of the negative electrode materials need to be improved, the electrolyte permeability and particle size distribution of the positive electrode materials need to be optimized, and the impact of electrolyte composition on battery performance also needs to be studied in depth.

Method used

Silicon-based anode material with a three-dimensional ordered shell-like structure and high-capacity lithium cobalt oxide positive electrode material, combined with a multi-functional electrolyte, silicon carbon anode material is prepared by refrigeration casting method, and lithium cobalt oxide positive electrode material is modified by coating and surfactant auxiliary method to form a micro-nano positive electrode material conducive to electrolyte penetration.

Benefits of technology

The long-term and stable circulation of high-specific lithium batteries is achieved, which improves the energy density and number of cycles of the battery in a low-temperature environment, and ensures the safety and mechanical stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725678A_ABST
    Figure CN119725678A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly discloses a high-specific-characteristic low-temperature secondary lithium battery which comprises a battery shell, a silicon-based negative electrode sealed in the battery shell, a lithium cobalt oxide positive electrode, a diaphragm arranged between the silicon-based negative electrode and the lithium cobalt oxide positive electrode, and a multifunctional electrolyte, wherein the material of the silicon-based negative electrode comprises a silicon-carbon main body, a carbon nanotube and graphene, and a three-dimensional ordered conchoidal structure is prepared and formed through a freezing casting method; the lithium cobalt oxide positive electrode material adopts improved redox graphene, a lithium cobalt oxide positive electrode plate is prepared by a coating method, and meanwhile, the lithium cobalt oxide positive electrode material is coated and modified by graphene by adopting a surfactant auxiliary method, so that the lithium cobalt oxide micro-nano positive electrode material beneficial to electrolyte permeation is formed. The lithium battery provided by the invention has the characteristics of good low-temperature performance, safety, high capacity and the like, long-term stable circulation of the lithium battery with high specific characteristic can be realized, and the power supply requirement of a field low-temperature environment is fully met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a low-temperature secondary lithium battery with high specific properties. Background Art

[0002] In the information age, with the rapid development of various electronic devices, electric vehicles and other fields, the requirements for battery performance continue to rise. The development of batteries with high reliability, high specific energy, high safety and good adaptability to high and low temperature environments has become a research focus in various countries.

[0003] At present, most common secondary batteries are lead-acid and lithium iron phosphate batteries. Although they have the advantages of safety and reliability, their energy density is low (all below 200Wh / kg), making it difficult to meet the high specific energy requirements. Existing lithium batteries have deficiencies in many aspects of performance, such as the structural stability and conductivity of negative electrode materials need to be improved, the electrolyte permeability and particle size distribution of positive electrode materials need to be optimized, and the impact of electrolyte composition on battery performance also needs to be further studied.

[0004] Among them, the negative electrode material is an important component of lithium-ion batteries, and its performance directly affects the overall performance of the battery. The negative electrode materials of lithium-ion batteries mainly include graphite and carbon-based materials, lithium titanate materials, silicon-based materials and lithium metal. As the most widely used commercial negative electrode material, graphite has excellent performance in lithium-ion batteries, but its low theoretical capacity (327mAh / g) limits the overall capacity. When new carbon materials such as carbon nanotubes and graphene are directly used as negative electrodes, there are problems such as high irreversible capacity, voltage hysteresis, and unclear discharge platform, which makes it difficult to meet the requirements of use. Lithium titanate has high safety performance, flat voltage platform, high chemical diffusion coefficient and coulomb efficiency, but low theoretical capacity (175mAh / g), poor conductivity, and serious capacity decay during high current charging and discharging. Silicon-based materials have extremely high specific capacity (4200mAh / g), but the volume changes greatly during charging and discharging (about 320%). Cyclic stress will destroy the electrode structure and cause capacity decay, which can be alleviated through strategies such as nanostructure design and silicon-carbon composite. The specific capacity of lithium metal negative electrode is extremely high (3860mAh / g), but the production process is complicated. During charging and discharging, dendrites will pierce the diaphragm, causing thermal runaway of the battery, poor safety performance, almost no commercial application, and low technical maturity.

[0005] Foreign batteries have accumulated a lot of experience and reliability data. Although China has carried out basic research on high-energy lithium batteries, it has not been applied. The key to improving battery energy density lies in the development of high-voltage, high-specific-capacity positive electrode materials and low-voltage, high-specific-capacity negative electrode materials. The current mainstream positive and negative electrode materials are lithium iron phosphate and graphite, with energy densities of only about 200Wh / kg. In addition, in the low-temperature cold environment outdoors, the battery energy drops sharply and it is difficult to meet the power supply needs.

[0006] In view of this, this invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a high specific low temperature secondary lithium battery with good low temperature performance, safety and large capacity.

[0008] The purpose of the present invention is to be solved by the following technical solutions:

[0009] In a first aspect, the present invention provides a high-specific-performance low-temperature secondary lithium battery, comprising a battery housing, a silicon-based negative electrode sealed in the battery housing, a lithium cobalt oxide positive electrode, a diaphragm and a multifunctional electrolyte separated between the silicon-based negative electrode and the lithium cobalt oxide positive electrode;

[0010] Among them, the material of the silicon-based negative electrode includes a silicon-carbon main body, carbon nanotubes and graphene, and a three-dimensional ordered shell-shaped negative electrode material is prepared by a freeze casting method; the material of the lithium cobalt oxide positive electrode adopts an improved redox graphene, and a lithium cobalt oxide positive electrode plate is prepared by a coating method, and at the same time, a surfactant-assisted method is used to coat and modify the lithium cobalt oxide positive electrode material with graphene, thereby forming a lithium cobalt oxide micro-nano positive electrode material that is conducive to the penetration of a multifunctional electrolyte.

[0011] Furthermore, the method for preparing the shell-shaped negative electrode material comprises the following steps:

[0012] 1) dissolving sodium carboxymethyl cellulose powder in an appropriate amount of deionized water, then adding graphene oxide suspension and carbon nanotube powder with hydroxyl groups, and stirring by magnetic force to fully disperse them to form a mixed suspension;

[0013] 2) adding silicon nanoparticles to the mixed suspension, and then stirring with a magnetic force to form a uniform slurry;

[0014] 3) Stir the slurry under vacuum to remove bubbles, and then pour it into a freeze casting device for freezing;

[0015] 4) The frozen sample is transferred to a freeze dryer to remove ice, and a black powdery substance is obtained. The black powdery substance is treated in an inert atmosphere and high temperature environment to reduce the graphene oxide, thereby obtaining a shell-shaped negative electrode material.

[0016] Furthermore, the lithium cobalt oxide micro-nano positive electrode material is a mixture of at least two spherical particles with different particle sizes.

[0017] Furthermore, the lithium cobalt oxide micro-nano positive electrode material comprises lithium cobalt oxide particles with a particle size of 100 nm to 300 nm and lithium cobalt oxide particles with a particle size of 5 μm to 6 μm.

[0018] Furthermore, the preparation method of the lithium cobalt oxide micro-nano positive electrode material comprises the following steps:

[0019] 1) After completing the surface passivation treatment of the high-capacity positive electrode material, the graphene in-situ loaded electrode material is prepared by combining in-situ composite and physical blending;

[0020] 2) Mix H2SO4 / H3PO4 solutions with a volume ratio of 9:1, add graphene powder and potassium permanganate in sequence under magnetic stirring, stir at 50°C for 12 hours, cool to room temperature and slowly pour into ice cubes, then add 30% H2O2 solution until the mixture turns golden yellow; then centrifuge and wash the golden solution with water, 10% HCl solution and ethanol in sequence to remove metal ions until the pH value is 5-6; finally, freeze-dry the yellow concentrated solution for 2-3 days to obtain GO powder;

[0021] 3) After the active material LiCoO2, conductive graphite and superconducting carbon are vacuum dried at 110°C for 24 hours, they are mixed with PVDF binder and NMP organic solvent, stirred in a sand mill to form positive electrode slurry. N2 is required for protection during the stirring process, and then evenly coated on the current collector aluminum foil by a coater. After drying, cutting and compacting, the positive electrode sheet is made;

[0022] 4) preparing a slurry, wherein the slurry components include: positive electrode LC108R particles of lithium cobalt oxide, PVDF, superconducting carbon, conductive graphite, graphene and NMP solvent.

[0023] Furthermore, the preparation method of the graphene in-situ loaded electrode material is as follows: first prepare functionalized graphene oxide; then evenly disperse and mix it with the passivated positive electrode material, perform hydrothermal or solvothermal treatment to make the positive electrode material evenly dispersed and attached to the surface of the graphene oxide sheet, and at the same time reduce the graphene oxide to graphene to prepare a graphene-passivation layer-positive electrode composite material, and after centrifugal washing and drying, form a graphene / electrode material micro-nano composite porous structure with high conductivity, and obtain a three-dimensional hierarchical porous electrode material based on graphene material.

[0024] Furthermore, the surfactant-assisted method is used to coat and modify the lithium cobalt oxide positive electrode material with graphene as follows: synthetic graphene oxide slurry and granular lithium cobalt oxide micro-nano positive electrode material are used as raw materials, and the cationic surfactant hexadecyl ammonium bromide is used to modify the surface of the lithium cobalt oxide micro-nano positive electrode material so that its surface carries a positive charge, and electrostatic interaction with the graphene oxide with negatively charged surface groups is generated to achieve coating, and then the graphene-coated modified lithium cobalt oxide positive electrode material is obtained through washing, filtering, drying and low-temperature thermal reduction.

[0025] Furthermore, the multifunctional electrolyte includes a solvent, a lithium salt and an additive, wherein the additive includes trifluoromethylethylene carbonate and lithium bis(fluorosulfonyl)imide, which are used to form a stable solid electrolyte interface SEI film on the electrode surface.

[0026] Furthermore, the parameters of the lithium battery are as follows: capacity is 3.2Ah, total weight is less than 48g, and energy density is 280wh / kg.

[0027] In a second aspect, the present invention provides an application of the above-mentioned high specific characteristic low temperature secondary lithium battery in mobile terminal products, electric vehicles and / or electric tools.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The lithium battery provided by the present invention is a high-energy-density lithium battery system constructed by matching a silicon-based negative electrode material with a three-dimensional ordered shell-like structure with a high-capacity lithium cobalt oxide positive electrode material and a multifunctional electrolyte, which can achieve long-term stable cycling of high-energy-density lithium batteries. In particular, the designed shell-like structure has the following multiple advantages:

[0030] The first is to limit the displacement and aggregation of silicon nanoparticles and enhance contact. By constructing a shell-like structure of vertically arranged graphene oxide sheets interconnected by carbon nanotubes, the displacement and aggregation of silicon nanoparticles are limited by the synergistic effect of chemical adsorption and heat treatment. During the charging and discharging process of lithium-ion batteries, the volume of silicon nanoparticles changes, which will affect the battery performance if not restricted. The shell-like structure not only limits the undesirable displacement and aggregation of particles, but also creates a strong and efficient contact between silicon and conductive reduced graphene oxide, ensuring the effective transmission of electrons and laying the foundation for the excellent electrochemical performance of the battery.

[0031] The second is to improve electronic conductivity. The carbon nanotubes vertically connected between adjacent reduced graphene oxides act as conductive pillars, improving the electronic conductivity perpendicular to the direction of reduced graphene oxide. In battery operation, the rapid transmission of electrons plays a key role in the charge and discharge rate and power performance. The unique conductive column design provides an efficient transmission channel for electrons, reduces transmission resistance, and enables the battery to have better performance in high-power output scenarios.

[0032] The third is to promote the rapid transport of lithium ions. Reduced graphene oxide has excellent ionic conductivity in the parallel direction, which promotes the rapid transport of lithium ions. During the charging and discharging process of lithium-ion batteries, the rapid migration of lithium ions is an important factor in ensuring performance. The shell-like structure of reduced graphene oxide sheets provides a fast channel for lithium ions, allowing lithium ions to quickly embed and detach from electrode materials, shortening the ion diffusion time and improving the battery charging and discharging efficiency and cycle performance.

[0033] Fourth, it has mechanical stability and provides expansion space. The shell-shaped electrode structure has excellent mechanical stability and provides expansion space for silicon nanoparticles. During the charge and discharge process, the volume change of silicon nanoparticles generates stress. If the mechanical stability of the electrode structure is insufficient, it will cause electrode rupture and capacity decay. The shell-shaped structure can withstand stress, protect the integrity of the electrode, provide space for the expansion of silicon nanoparticles, relieve internal stress, and extend the service life of the battery.

[0034] The fifth is to provide more reaction sites and improve performance. The unique loose three-dimensional structure provides more reaction sites during the charge and discharge process, shortening the distance of lithium ion embedding and extraction from silicon. More reaction sites improve electrochemical activity, improve battery power performance and energy density. At the same time, it shortens the ion transmission distance, reduces the diffusion time, improves the electrode power performance and low-temperature charge and discharge performance, and enables the battery to have excellent performance in various environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0037] Figure 1 This is a block diagram of the high specific characteristics and low temperature secondary lithium battery solution of the present invention;

[0038] Figure 2 It is a block diagram of the preparation and modification of the positive electrode material of the present invention;

[0039] Figure 3 This is a block diagram of a method for preparing a high-capacity positive electrode sheet based on graphene materials according to the present invention;

[0040] Figure 4 This is a block diagram of the multifunctional electrolyte solution of the present invention. DETAILED DESCRIPTION

[0041] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples consistent with some aspects of the present invention as detailed in the appended claims.

[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0043] See also Figures 1 to 4 , a high-specific-performance low-temperature secondary lithium battery provided by an embodiment of the present invention comprises a battery housing, and a silicon-based negative electrode, a lithium cobalt oxide positive electrode, a diaphragm and a multifunctional electrolyte separated between the silicon-based negative electrode and the lithium cobalt oxide positive electrode sealed in the battery housing. Among them, the material of the silicon-based negative electrode comprises a silicon-carbon main body, carbon nanotubes and graphene, and a three-dimensional ordered shell-shaped negative electrode material is prepared by a freeze casting method; the material of the lithium cobalt oxide positive electrode adopts an improved redox graphene, and a lithium cobalt oxide positive electrode sheet is prepared by a coating method, and a surfactant-assisted method is used to coat and modify the lithium cobalt oxide positive electrode material with graphene, thereby forming a lithium cobalt oxide micro-nano positive electrode material that is conducive to the penetration of a multifunctional electrolyte. In other words, the present invention mainly combines a silicon negative electrode material with a three-dimensional ordered shell-like structure with a high-capacity positive electrode material, and a multifunctional electrolyte to construct a high-specific-energy lithium battery system, so that a stable cycle of a high-specific-performance lithium battery at low temperature can be achieved.

[0044] Specifically in the embodiment of the present invention, the silicon-based negative electrode selects the silicon-carbon main body as the core framework, and constructs it to present a loose three-dimensional structure. This structural design is intended to lay the foundation for subsequent performance improvement. In order to further optimize the electrical properties of the material, carbon nanotubes and graphene are introduced into the silicon-carbon main body. The addition of carbon nanotubes and graphene significantly improves the overall ion migration rate and conductivity of the material, and provides a more efficient channel for the transmission of electrons and ions. At the same time, the present invention adopts a freeze casting method to prepare a silicon negative electrode material with a shell-like structure. This method uses ice as a template, makes full use of the physical properties of ice, and provides a unique environment for material molding. Among them, graphene serves as a builder of a two-dimensional layered structure, while carbon nanotubes play a key role in connecting graphene sheets. The two work together to finally obtain a silicon-carbon negative electrode material with a three-dimensional ordered structure. By constructing graphene oxide sheets interconnected and vertically arranged with carbon nanotubes, a unique structure similar to a shell shape is designed. This innovative structural design successfully solves many problems brought about by thick electrodes in practical applications. The distance of lithium ions embedded in the silicon negative electrode is effectively shortened, allowing lithium ions to reach the reaction site more quickly, greatly increasing the reactive sites of the silicon negative electrode, and significantly improving the low-temperature lithium embedding capacity of the silicon negative electrode. Ultimately, the long-term stable cycle of the ultra-high load silicon negative electrode is achieved, providing a new solution and technical path for the performance optimization of silicon-based negative electrode materials in practical applications.

[0045] The method for preparing the shell-shaped negative electrode material in the embodiment of the present invention comprises the following steps:

[0046] 1) Dissolve 300 g of sodium carboxymethyl cellulose powder in an appropriate amount of deionized water, then add 14.28 g of graphene oxide suspension (1.4% wt%) and 100 mg of carbon nanotube powder with hydroxyl groups, and stir magnetically for 1 hour to ensure that they are fully dispersed;

[0047] 2) adding 800 mg of silicon nanoparticles to the mixed suspension, and then magnetically stirring for 6 hours to form a uniform slurry;

[0048] 3) Stir the slurry under vacuum for 30 minutes to remove bubbles, pour it into a freeze casting device and freeze it for 5 minutes;

[0049] 4) The frozen sample was transferred to a freeze dryer for 48 hours to remove ice, and a black powdery substance was obtained. The black powdery substance was treated at 900° C. for 2 hours in an inert atmosphere to reduce the graphene oxide, thereby obtaining a shell-shaped silicon-carbon negative electrode material.

[0050] In an embodiment of the present invention, the material of the lithium cobalt oxide positive electrode adopts improved redox graphene (GO), and the lithium cobalt oxide positive electrode plate is prepared by a coating method. At the same time, a surfactant-assisted method is used to coat and modify the lithium cobalt oxide positive electrode material with graphene, and finally a lithium cobalt oxide micro-nano positive electrode material composed of micro-nano particles is formed.

[0051] Specifically, the preparation method of the lithium cobalt oxide micro-nano positive electrode material composed of micro-nano particles in the embodiment of the present invention is as follows:

[0052] 1) After the surface passivation treatment of the high-capacity positive electrode material is completed, the graphene in-situ loaded electrode material is prepared by combining in-situ compounding (including hydrothermal method, solvothermal method, etc.) and physical blending (including wet ball milling, dry ball milling, etc.). Specifically, 1.1) functionalized graphene oxide is first prepared, 1.2) it is then uniformly dispersed and mixed with the passivated positive electrode material, and hydrothermal or solvothermal treatment is performed to make the positive electrode material uniformly dispersed and attached to the surface of the graphene oxide sheet, and the graphene oxide is reduced to graphene to prepare a graphene-passivation layer-positive electrode composite material, which is centrifugally washed and dried to form a graphene / electrode material micro-nano composite porous structure with high conductivity, and a three-dimensional hierarchical porous electrode material based on graphene material is prepared.

[0053] 2) Mix H2SO4 / H3PO4 solutions with a volume ratio of 9:1, add graphene powder and potassium permanganate in sequence under magnetic stirring, and stir at 50°C for 12 hours. After cooling to room temperature, slowly pour into ice cubes, and then add 30% H2O2 solution until the mixture turns golden yellow; then the golden solution is continuously centrifuged and washed with water, 10% HCl solution and ethanol in sequence to remove metal ions until the pH value is about 5-6; finally, the yellow concentrated solution is freeze-dried for 2-3 days to obtain GO powder.

[0054] ③ After the active material LiCoO2, conductive graphite and superconducting carbon are vacuum dried at 110°C for 24 hours, they are mixed with PVDF binder and NMP organic solvent, and stirred in a sand mill to form positive electrode slurry. N2 is required for protection during the stirring process, and then it is evenly coated on the current collector aluminum foil using a coater. After drying, cutting and compacting, the positive electrode sheet is made.

[0055] ④ Prepare the slurry, the formula is: positive electrode LC108R small particle lithium cobalt oxide: 300g 90%, PVDF (10%) 100g 3%, superconducting carbon (Sp) 14g 4%, conductive graphite 7g 2%, graphene 60g (ultrasonic dispersion for 2 hours before use) 1%, NMP100g solvent. ⑤ The lithium cobalt oxide micro-nano positive electrode material mainly includes micron-level particles of about 5 to 6 microns and 100-300 nanometer-level particles. In other words, compared with the conventional lithium cobalt oxide positive electrode material with a commercial particle size of 10 microns, the present invention has a micro-nano structure containing nano-level particles with obvious layered graphene distributed in the positive electrode material, which can effectively coat and modify the positive electrode material, is more conducive to electrolyte penetration in terms of electrical properties, and has better rate performance.

[0056] Furthermore, a surfactant-assisted method is used to coat and modify the lithium cobalt oxide positive electrode material with graphene. The basic process is to use synthetic graphene oxide (GO) slurry and small-particle lithium cobalt oxide micro-nano positive electrode material as raw materials, and use cationic surfactant hexadecylammonium bromide (CTAB) to modify the surface of the lithium cobalt oxide micro-nano positive electrode material so that its surface carries positive charge, and electrostatic interaction with graphene oxide (GO) with negatively charged surface groups is achieved to achieve coating, and then the graphene-coated modified lithium cobalt oxide positive electrode material is obtained through washing, filtering, drying and low-temperature thermal reduction. The specific synthesis process is as follows: 10g of lithium cobalt oxide micro-nano positive electrode material is dispersed in 1000mL of deionized water, 0.5% CTAB by solvent mass is added, stirring is performed for 0.5h and ultrasonic treatment is performed for 1h, the pH of the mixed solution is adjusted to 3-4 using 10% HCl solution, and 0.2mg / mL of GO slurry obtained by Hummers method is slowly added to obtain a lithium cobalt oxide micro-nano positive electrode material coated with graphene oxide with a mass fraction of 4%. After washing, filtering, drying and grinding, the material is reduced at 250°C for 10min to obtain a graphene-coated modified lithium cobalt oxide positive electrode material.

[0057] In the embodiment of the present invention, the multifunctional electrolyte can pre-form a dense and stable passivation film on the surface of the electrode material, increase the interface stability between the electrode material and the electrolyte during the cycle, and inhibit the chemical side reactions of the electrolyte itself during the cycle. The preparation method is as follows: 1) Using the additives in the electrolyte, combined with the optimized pre-formation control technology, a SEI film with controllable properties is formed on the electrode surface to improve the cycle stability of the battery, while making its impedance (ion conduction) meet the battery power performance requirements; 2) Through the optimization of the electrolyte formula, especially the type and proportion of additives, and the control of the pre-formation process, the additives are pre-formed on the surface of the electrode material. A dense and stable passivation film is increased, and the interface stability between the electrode material and the electrolyte during the cycle; 3) The chemical side reactions of the electrolyte itself are inhibited during the cycle, thereby improving the stability and cycle performance of the battery.

[0058] In summary, the three-dimensional ordered shell-like structured silicon-based negative electrode material, high-capacity lithium cobalt oxide positive electrode material and multifunctional electrolyte obtained by the above-mentioned preparation method of the present invention are finally assembled into a battery. The obtained secondary lithium battery has a capacity of 3.2Ah, a total weight of less than 48g, and an energy density of 280wh / kg after actual testing. It can achieve a specific energy of 280wh / kg (0.2C) and a cycle number of 2000 times under low temperature environment.

[0059] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.

[0060] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A high specific performance low temperature secondary lithium battery, characterized in that: The invention comprises a battery shell, a silicon-based negative electrode sealed in the battery shell, a lithium cobalt oxide positive electrode, a diaphragm and a multifunctional electrolyte separated between the silicon-based negative electrode and the lithium cobalt oxide positive electrode; Among them, the material of the silicon-based negative electrode includes a silicon-carbon main body, carbon nanotubes and graphene, and a three-dimensional ordered shell-shaped negative electrode material is prepared by a freeze casting method; the material of the lithium cobalt oxide positive electrode adopts an improved redox graphene, and a lithium cobalt oxide positive electrode plate is prepared by a coating method, and at the same time, a surfactant-assisted method is used to coat and modify the lithium cobalt oxide positive electrode material with graphene, thereby forming a lithium cobalt oxide micro-nano positive electrode material that is conducive to the penetration of a multifunctional electrolyte.

2. The high specific performance low temperature secondary lithium battery according to claim 1, characterized in that: The method for preparing the shell-shaped negative electrode material comprises the following steps: 1) dissolving sodium carboxymethyl cellulose powder in an appropriate amount of deionized water, then adding graphene oxide suspension and carbon nanotube powder with hydroxyl groups, and stirring by magnetic force to fully disperse them to form a mixed suspension; 2) adding silicon nanoparticles to the mixed suspension, and then stirring with a magnetic force to form a uniform slurry; 3) Stir the slurry under vacuum to remove bubbles, and then pour it into a freeze casting device for freezing; 4) The frozen sample is transferred to a freeze dryer to remove ice, and a black powdery substance is obtained. The black powdery substance is treated in an inert atmosphere and high temperature environment to reduce the graphene oxide, thereby obtaining a shell-shaped negative electrode material.

3. The high specific performance low temperature secondary lithium battery according to claim 1, characterized in that: The lithium cobalt oxide micro-nano positive electrode material is a mixture of at least two spherical particles with different particle sizes.

4. The high specific performance low temperature secondary lithium battery according to claim 3, characterized in that: The lithium cobalt oxide micro-nano positive electrode material comprises lithium cobalt oxide particles with a particle size of 100nm to 300nm and lithium cobalt oxide particles with a particle size of 5μm to 6μm.

5. The high specific performance low temperature secondary lithium battery according to claim 1, characterized in that: The preparation method of the lithium cobalt oxide micro-nano positive electrode material comprises the following steps: 1) After completing the surface passivation treatment of the high-capacity positive electrode material, the graphene in-situ loaded electrode material is prepared by combining in-situ composite and physical blending; 2) Mix H2SO4 / H3PO4 solutions with a volume ratio of 9:1, add graphene powder and potassium permanganate in sequence under magnetic stirring, stir at 50°C for 12 hours, cool to room temperature and slowly pour into ice cubes, then add 30% H2O2 solution until the mixture turns golden yellow; then the golden solution is continuously centrifuged and washed with water, 10% HCl solution and ethanol in sequence to remove metal ions until the pH value is 5-6; finally, the yellow concentrated solution is freeze-dried for 2-3 days to obtain GO powder; 3) After the active material LiCoO2, conductive graphite and superconducting carbon are vacuum dried at 110°C for 24 hours, they are mixed with PVDF binder and NMP organic solvent, stirred in a sand mill to form positive electrode slurry. N2 is required for protection during the stirring process, and then evenly coated on the current collector aluminum foil by a coater. After drying, cutting and compacting, the positive electrode sheet is made; 4) preparing a slurry, wherein the slurry components include: positive electrode LC108R particles of lithium cobalt oxide, PVDF, superconducting carbon, conductive graphite, graphene and NMP solvent.

6. The high specific performance low temperature secondary lithium battery according to claim 5, characterized in that: In step 1), the preparation method of the graphene in-situ loaded electrode material is as follows: first prepare functionalized graphene oxide; then evenly disperse and mix it with the passivated positive electrode material, perform hydrothermal or solvothermal treatment to make the positive electrode material evenly dispersed and attached to the surface of the graphene oxide sheet, and reduce the graphene oxide to graphene to prepare a graphene-passivation layer-positive electrode composite material, and after centrifugal washing and drying, form a graphene / electrode material micro-nano composite porous structure with high conductivity, and obtain a three-dimensional hierarchical porous electrode material based on graphene material.

7. The high specific performance low temperature secondary lithium battery according to claim 1, characterized in that: The process of coating and modifying lithium cobalt oxide positive electrode materials with graphene using a surfactant-assisted method is as follows: synthetic graphene oxide slurry and granular lithium cobalt oxide micro-nano positive electrode materials are used as raw materials, and the surface of the lithium cobalt oxide micro-nano positive electrode materials is modified using a cationic surfactant cetyl ammonium bromide, so that the surface of the lithium cobalt oxide micro-nano positive electrode materials carries a positive charge, and electrostatic interaction occurs with the graphene oxide with negatively charged surface groups to achieve coating, and then the graphene-coated modified lithium cobalt oxide positive electrode material is obtained through washing, filtering, drying and low-temperature thermal reduction.

8. The high specific performance low temperature secondary lithium battery according to claim 1, characterized in that: The multifunctional electrolyte comprises a solvent, a lithium salt and an additive, wherein the additive comprises trifluoromethylethylene carbonate and lithium bis(fluorosulfonyl)imide, and is used for forming a stable solid electrolyte interface SEI film on the surface of an electrode.

9. The high specific performance low temperature secondary lithium battery according to any one of claims 1 to 8, characterized in that: The parameters of the lithium battery are as follows: capacity is 3.2Ah, total weight is less than 48g, and energy density is 280wh / kg.

10. Application of a high specific characteristic low temperature secondary lithium battery according to any one of claims 1 to 9 in mobile terminal products, electric vehicles and / or electric tools.